Confirmatory Study of Time-Dependent Computed Tomographic Perfusion Thresholds for Use in Acute Ischemic Stroke. Issue 11 (November 2019) - Qiu, Wu; Kuang, Hulin; Lee, Ting Y.; Boers, Anna M.; Brown, Scott; Muir, Keith; Majoie, Charles B.L.M.; Dippel, Diederik W.J.; White, Phil; Guillemin, Francis; Mitchell, Peter J.; Dávalos, Antoni; et al.
Abstract : Background and Purpose—: Computed tomographic perfusion (CTP) thresholds associated with follow-up brain infarction may differ by time from symptom onset to imaging and reperfusion. We confirm CTP thresholds over time to imaging and reperfusion in patients with acute ischemic stroke from the HERMES collaboration (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials) data. Methods—: Patients with occlusion on CT angiography were acutely imaged with CTP. Noncontrast CT and magnetic resonance-diffusion weighted imaging at 24 to 48 hours defined follow-up infarction. Reperfusion was assessed on conventional angiogram. Tmax, cerebral blood flow (CBF), and cerebral blood volume maps were derived from delay-insensitive CTP postprocessing. These parameters were analyzed using receiver operator characteristics to derive optimal thresholds based on time from stroke onset-to-CTP or to reperfusion. ANOVA and linear regression were used to test whether the derived CTP thresholds were different by time. Results—: One hundred thirty-seven patients were included. Tmax thresholds of >15.7 s and >15.8 s and absolute CBF thresholds of <8.9 and <7.5 mL·min −1 ·100 g −1 for gray matter and white matter respectively were associated with infarct if reperfusion was achieved <90 minutes from CTP with stroke onset-to-CTP <180 minutes. The discriminative ability of cerebral blood volume was modest. There were no statistically significant relationships between stroke onset-to-CTP time and Tmax, CBF, and cerebral blood volume thresholds (all P >0.05). A statistically significant relationship was observed between CTP-to-reperfusion time and the optimal thresholds for Tmax ( P <0.001) and CBF ( P <0.001). Similar but more modest relationship was noted for onset-to-reperfusion time and optimal thresholds for CBF ( P ⩽0.01). Conclusions—: CTP thresholds based on stroke onset and imaging time and taking into account time needed for reperfusion may improve infarct prediction in patients with acute ischemic stroke. Abstract : Supplemental Digital Content is available in the text.